Crystal chemistry and X-ray diffraction patterns for Co(NixZn1−x)Nb4O12 (x = 0.2, 0.4, 0.6, 0.8). Issue 4 (12th October 2016) - Liu, G.; Wong-Ng, W.; Kaduk, J. A.
Abstract : X-ray reference powder patterns and structures have been determined for a series of cobalt-, nickel- and zinc-containing niobates, Co(Ni x Zn1− x )Nb4 O12 ( x = 0.2, 0.4, 0.6, 0.8). The Co(Ni x Zn1− x )Nb4 O12 series crystallize in the space group of Pbcn, which is of the disordered columbite-type structure ( α -PbO2 ). The lattice parameters range from a = 14.11190(13) to 14.1569(3) Å, b = 5.69965(6) to 5.71209(13) Å, c = 5.03332(5) to 5.03673(11) Å, and V = 404.844(8) to 407.296(17) Å 3 from x = 0.8 to 0.2, respectively. Co(Ni x Zn1− x )Nb4 O12 contains double zig-zag chains of NbO6 octahedra and single chain of (Ni, Zn, Co)O6 octahedra run parallel to the bc -plane. Within the same chain the NbO6 octahedra share edges, while the adjacent NbO6 chains are joined to each other through common oxygen corners. These double NbO6 chains are further linked together along the [100]-direction through another (Co, Ni, Zn)O6 units, via common oxygen corners. The edge-sharing (Co, Ni, Zn)O6 also forms zig-zag chains along the c -axis. Powder X-ray diffraction patterns of this series of compounds have been submitted to be included in the Powder Diffraction File.